Synovial sarcoma of the mandible - Maryam Khalili; Nosratollah Eshghyar; Fereshteh Ensani; Pouyan Amini Shakib (Journal of Research in Medical Sciences, 2012)
Synovial sarcoma (SS) is a relatively common soft tissue tumor but only 6%-7% of cases are diagnosed in the head and neck region. It typically occurs in young adults and is slightly more common in males. The most common sites in the head and neck region are hypopharynx and parapharyngeal spaces. However, SS can also occur in tonsils, tongue, and orofacial soft tissues. It is not difficult to diagnose SS microscopically with its classic biphasic appearance, but the diagnosis of monophasic forms is more challenging especially in unusual locations. In this article, we report a rare case of monophasic SS of the mandible. The clinical, histopathological, and immunohistochemical features are discussed and compared with previously reported cases in the literature. To our knowledge, only six primary involvements have been reported in the jaws. Therefore, our case represents the seventh reported case of SS in the area.